Incorporation of Ursolic Acid in Liquid Crystalline Systems Improves the Antifungal Activity Against Candida Sp - Marena, Gabriel Davi [UNESP]; Fonseca-Santos, Bruno [UNESP]; Matheus Aparecido dos Santos, Ramos [UNESP]; dos Santos, Karen Cristina [UNESP]; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2020)
Purpose: Infectious diseases caused by Candida sp. have high drug resistance due to the uncontrolled use of antibiotics. Among the natural products, ursolic acid (UA), a triterpene, has been increasing interest due to its antimicrobial effects. However, the physicochemical properties of UA, such as its low aqueous solubility, lead to failure of therapeutic application. Because of this, drug release systems, such as liquid crystals (LCs), can improve solubilization and increase the therapeutic efficacy of many drugs. Methods: In this work, we evaluated the antifungal potential of UA and loaded into LC precursor system against Candida sp. The system was composed of oleic acid (30%), polysorbate 80 (60%), and purified water (10%). Polarized light microscopy, rheological assays, and simulated vaginal fluid (SVF) simulations were performed. Cytotoxicity assay was evaluated against L-929 cells (murine fibroblast), and antifungal evaluation was performed by microplate microdilution method against Candida albicans, Candida glabrata, Candida krusei, Candida parapsilosis, and Candida tropicalis. Results: The system showed acceptable parameters for UA incorporation, such as adhesiveness, texture, and flow behaviors, compatible to vaginal administration. Free UA showed no antifungal activity; however, after incorporation into LCs, it was observed against C. albicans, C. glabrata, C. tropicalis, and C. parapsilosis (MIC values around 500 μg/mL and 3.9 μg/cell viability assays showed moderate cytotoxicity [halo diameter 1.00 ± 0.156]). Conclusion: In conclusion, the results corroborate in the materials field as a possible alternative in the treatment of infectious diseases by Candida species and the systems showed potential promising for enhancing AU antifungal performance with the application on vulvovaginitis.
Keywords: Candida species; Fungal infections; Liquid crystal system; Nanotechnology; Ursolic acid